Faith, Praxis, and Practical Theology: At the Interface of Sociology and Theology - Lawler, Michael G. (Horizons, 2002)
This essay is an exercise in practical theology, the theological reflection arising out of and in response to the church's actual situation. Practical theology insists that it is not enough to analyze the church's actual situation with deductive, ahistorical theological principles, but that it is necessary, first, to uncover and, then, reflect critically on the actual situation to test it for the presence of the Spirit, relevance, and significance in light of the gospel. Practical theology grows out of the relationship between theoria and praxis which, for the church, is the relationship between faith and praxis. The essay argues that to recognize scientifically the church's actual situation and to perform the required theological reflection practical theology requires sociology.The essay explores, therefore, the relationship between practical theology and the data of sociological research. It also examines the theological realities, sensus fidei and reception, and explores their relationship to that data. The exploration is concretized theologically by a consideration of the sociological data and theology about two Catholic moral doctrines, divorce and remarriage without prior annulment and artificial contraception. A theological reflection on the actual situation of both doctrines and a sociological consideration of the data suggest the conclusion that a dramatic development and re-reception of both doctrines, in line with previous dramatic developments of doctrine in the church, is under way.